Maximum Electricity Production Time from Tofu Whey using Microbial Fuel Cell - Prasidha, Willie (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
This study was aimed at evaluating the performance of double chamber microbial fuel cell from tofu whey. The value of open circuit voltage (OCV) and surrounding temperature were taken at four different time which were 6 am, 12 pm, 6 pm, and 12 am. A double chamber microbial fuel cells (MFC) with different was developed to produce electricity from tofu whey and studied for 7 days. Anode and cathode were made by uncoated graphite rod. After 7 days, the electricity production characteristics at four different time were obtained. The results show that the average maximum OCV was reached at 6 pm during the MFC operation. This study also indicated that higher surrounding temperature provide higher electricity production. The optimum surrounding temperature of this study was 31ËšC.